E-046 Venous sinus stenting as a treatment approach in patients with idiopathic intracranial hypertension and encephaloceles. (22nd July 2019) - Drocton, G; Copelan, A; Amans, M; Khangura, R; Villanueva-Meyer, J; Eisenmenger, L; Meisel, K
Abstract : Introduction: Brain herniations, or encephaloceles, into arachnoid granulations in dural venous sinuses have rarely been reported in the literature. Prominent arachnoid granulations by themselves may be a cause of idiopathic intracranial hypertension (IIH) by obstructing sinus venous flow as well as causing flow turbulence that may present itself clinically with pulse synchronous tinnitus. This unique type of encephalocele combined with idiopathic intracranial hypertension (IIH) is an unreported occurrence and the optimal management in this rare subselect group of patients is unknown. Materials and methods: A retrospective review of 256 cases of IIH over a three-year span (March 2016 to March 2019) was performed at our institution. Imaging from the cases was reviewed by two trained diagnostic neuroradiologists assessing for the presence and location of dural sinus arachnoid granulations and/or encephaloceles based on MRI. Those patients that were found to have arachnoid granulations and concomitant encephalocele were documented and a clinical chart review was performed. Results: Of the 256 reviewed cases, 15 were found to have encephaloceles on MR imaging. 2 of the 15 cases had medically refractory IIH and underwent venous sinus stenting for management of their symptoms. Patient A is a 44 year-old female with symptoms of pulsatile tinnitus, papilledema, and elevated CSF opening pressure. Venography revealed bilateral transverse sinus stenoses (right side greater than the left) and a significant pressure gradient on the right side. Dilation of the right transverse sinus with a single stent resulted in a decreased pressure gradient across the arachnoid granulation. Clinical follow-up at 2 years after treatment revealed complete resolution of her symptoms. Retrospective review of her pre-procedure MRI revealed bilateral encephaloceles into prominent arachnoid granulations. Patient B is a 45 year-old male with progressive vision loss, papilledema, and headaches refractory to medical management whom underwent stenting in a right dominant transverse sinus. Venography at the time of stenting revealed bilateral transverse sinus stenoses (left side greater than the right) with significant pressure gradients on both sides. Clinical follow-up at 4 months after treatment revealed a full recovery. Retrospective review of his pre-procedure MRI demonstrated narrowing of the left transverse sinus due to an encephalocele into an arachnoid granulation. Conclusion: Venous sinus stenting is a unique and unreported treatment approach for patients with IIH and concomitant encephaloceles. We present two cases successfully treated with venous stenting. Disclosures: G. Drocton: None. A. Copelan: None. M. Amans: None. R. Khangura: None. J. Villanueva-Meyer: None. L. Eisenmenger: None. K. Meisel: None.